Digitally Down to the Countryside: Fintech and Rural Development in China. Issue 10 (3rd October 2021) - Kong, Sherry Tao; Loubere, Nicholas
Abstract: Digital finance has changed the landscape of financial service provision worldwide. China in particular, with a booming fintech sector and large numbers of users, is at the forefront of the expansion of digital financial services. As such, the country has become an important case for better understanding how fintech operates and what its expansion entails for socioeconomic development. This paper focuses on the provision of new models of digital finance in rural China by two Internet giants – JD and Alibaba. Against the backdrop of decades of generally unsuccessful attempts to expand financial coverage in rural areas by conventional bricks-and-mortar financial institutions, these two rural fintech models have the potential to expand digital financial service provision in new ways. This paper critically examines these fintech models, contextualises them within the broader trajectory of pushes to expand digital financial inclusion worldwide, considers the parallels with agricultural supplier contracting systems elsewhere, and explores the potential benefits and risks that they pose for rural development and rural livelihoods in China and elsewhere.